PERKEMBANGAN TEKNOLOGI SENJATA DAN PRINSIP PROPORSIONALITAS - Erlies Septiana Nurbani (Jurnal IUS Kajian Hukum dan Keadilan, 2017)
This research seeks to answer the question of how the role of humanitarian law in regulate the development of weapons technology and its relationship with the principle of proportionality. This research is normative research which used statute approach and conceptual approach. War can not be separated from the technology development. Weapons technology development concomitant with the development of human civilization. The basic principle is man use weapons according to his time. Martin van Creveld identifiy the clasification of  weapon history into four phases, are  age of tools, age of machines, age of system, and age of automation. This development definitely have correlation between the impact of  development of weapons technology and human behaviour in war.The more modern weapons systems used in war  the more casualties and losses generated by the war. International humanitarian law purposes is to minimize the effects. The principle of proportionality is expected to be the direction for the parties to consider any attack not to be devastating, especially to the civilian although the written humanitarian law haven’t accommodate the use of weapons as the result of war technology development, yet.